ROLE OF THE RENAL MICROCIRCULATION IN PROGRESSION OF CHRONIC KIDNEY INJURY IN OBESITY - Chade, Alejandro R. (Am J Nephrol, 2016)
BACKGROUND: Obesity is largely responsible for the growing incidence and prevalence of diabetes, cardiovascular, and renal disease. Current strategies to prevent and treat obesity and its consequences have been insufficient to reverse the ongoing trends. Lifestyle modification or pharmacological therapies often produce modest weight loss which is not sustained and recurrence of obesity is frequently observed, leading to progression of target organ damage in many obese subjects. Therefore, research efforts have focused not only on the factors that regulate energy balance, but also on understanding mechanisms of target organ injury in obesity. SUMMARY AND KEY MESSAGE: Microvascular disease plays a pivotal role in progressive kidney injury from different etiologies such as hypertension, diabetes, and atherosclerosis, which are all important consequences of chronic obesity. The microvascular networks are anatomical units that are closely adapted to specific functions of nutrition and removal of waste in every organ. Damage of the small vessels in several tissues and organs has been reported in obesity and may increase cardio-renal risk. However, the mechanisms by which obesity and its attendant cardiovascular and metabolic consequences interact to cause renal microvascular injury and chronic kidney disease are still unclear, although substantial progress has been made in recent years. This review addresses potential mechanisms and consequences of obesity-induced renal microvascular injury as well as current treatments that may provide protection of the renal microcirculation and slow progressive kidney injury in obesity.